Is neurofilament light chain useful as a disease progression marker for ATTRv amyloidosis? A literature review - Sekijima, Yoshiki; Ueda, Mitsuharu; Kitaoka, Hiroaki; Takahashi, Kentaro (Rinsho Shinkeigaku, 2025)
ATTRv amyloidosis is an autosomal-dominant disorder characterized by mutations in the transthyretin (TTR) gene, systemic deposition of transthyretin amyloid fibrils, and progressive polyneuropathy. Current scoring systems developed for ATTRv amyloidosis to measure the severity of polyneuropathy are not sufficiently sensitive or are difficult to implement in daily practice. Results of phase 3 trials for oligonucleotide therapeutics and real-world evidence have shown that neurofilament light chain (NfL), a key structural component of axons, is a reliable blood biomarker for assessing disease progression and treatment response in patients with ATTRv amyloidosis with polyneuropathy. Because blood NfL levels can be affected by factors such as age, body mass index (BMI), and renal function, its significance in patient monitoring needs to be assessed carefully while considering the clinical characteristics of each patient.